2020
DOI: 10.1021/acsanm.0c01939
|View full text |Cite
|
Sign up to set email alerts
|

Binary Zn-Doped SnO2/Al2O3 Nanotube Composites for Visible-Light-Driven Photocatalytic Degradation of Basic Blue 41

Abstract: Binary Zn-doped SnO2/Al2O3 nanotube (NT) composites were synthesized for visible-light-driven photocatalytic degradation of Basic Blue 41 (BB41) through an environmentally friendly and low-cost liquid phase deposition (LPD) process. The results indicated that Zn-doping with SnO2 nanotubes and coupling with alumina membranes could improve the photocatalytic degradation efficiency under present conditions. In this research, the synthesized Zn-doped SnO2/Al2O3 NT composites demonstrated higher photocatalytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…It is an attractive and a better alternative to the conventional powder nanophotocatalysts in water purification [147][148][149][150][151]. Using this strategy, different authors reported Al 2 O 3 -based photocatalytic membranes for the removal of dyes [147,152], pharmaceuticals [153] and Reprinted with permission from [156] heavy metals [154], and even for virus inactivation [155]. Nevertheless, the design of such ceramic nanocomposite membranes requires precise control over the modification of alumina's surface (using coating techniques like spincoating, drop-casting, and atomic layer deposition) to allow uniform deposition and high photocatalytic performance without hindering or affecting water permeability [141,144,155].…”
Section: Al 2 O 3 -Based Inorganic Supportsmentioning
confidence: 99%
“…It is an attractive and a better alternative to the conventional powder nanophotocatalysts in water purification [147][148][149][150][151]. Using this strategy, different authors reported Al 2 O 3 -based photocatalytic membranes for the removal of dyes [147,152], pharmaceuticals [153] and Reprinted with permission from [156] heavy metals [154], and even for virus inactivation [155]. Nevertheless, the design of such ceramic nanocomposite membranes requires precise control over the modification of alumina's surface (using coating techniques like spincoating, drop-casting, and atomic layer deposition) to allow uniform deposition and high photocatalytic performance without hindering or affecting water permeability [141,144,155].…”
Section: Al 2 O 3 -Based Inorganic Supportsmentioning
confidence: 99%
“…Because of their quantum confinement effects and a high‐specific surface area, one‐dimensional nanostructures can provide a large number of surface‐reactive sites for photocatalytic reactions, high light absorption efficiency, and directional transport of photogenerated charge carriers. Thus, they are useful for enhancing photocatalytic performance, as reported in our previous works 2,14,15 …”
Section: Introductionmentioning
confidence: 64%
“…1 One of the most dangerous dyes is Basic Blue 41 (BB 41), which is typically used for dyeing silk, wool, cotton, and acrylic. 2 This dye is potentially fatal to living organisms as it may cause respiratory irritation, nausea, diarrhea, vomiting, excessive perspiration, methemoglobinemia, and mental disorientation. 3 Thus, many scientific and technological efforts have been devoted to achieving effective strategies for treating wastewater containing dyes in recent decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For extensive degradation of Basic blue 41, Abbas Attar developed Zn-SnO 2 /Al 2 O 3 nanotubes using a liquid-phase deposition process. 213 The dye was degraded efficiently under visible light irradiation, and the enhanced performance was due to the high specific area, wide visible-light absorption range, narrowed bandgap by Zndoping, and effective electron-hole separation.…”
Section: Applications Of Snomentioning
confidence: 99%